The role of the court and the parties to the judicial examination of the accused, witnesses and victims under the new Criminal Procedural Code of Ukraine 2012 - Костюченко, О.Ю. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2015)
The article defines the essence of the terms “direct” and “cross-examination” of witnesses and victims. It is noted that during the trial, the examination of witnesses does not involve the use of a free form of presentation but rather responses to questions, while the option of free presentation regarding evidence applies only to the questioning of the accused. Prosecutors and defense counsel, in the trial of criminal proceedings, to ensure the performance of their procedural functions of prosecution and defense, should pay special attention to compliance with the procedural order, as well as the correct strategy and tactics of direct and cross-examination of witnesses and victims, as the broader use of adversarial elements under the new Criminal Procedure Code of Ukraine increases the likelihood of obtaining necessary information from the person being questioned to verify the legal positions of the parties. It is noted that the court does not conduct the questioning but only monitors compliance with the rules of its implementation by the parties. The judge may, upon objection from the parties, reject questions that do not pertain to the merits of the criminal proceedings and, in case of ambiguity in the testimony of a witness or victim regarding the presence or absence of specific circumstances, require the witness to provide a clear answer to the question – “yes” or “no”; however, the presiding judge may ask questions only after the witness has been questioned by the victim, civil plaintiff, civil defendant, their representatives, and legal representatives or during the examination of other evidence. The issue of the participation of the accused (defendant) in the “direct” and “cross-examination” of witnesses and victims is considered in light of the provisions of international conventions and the practice of the European Court of Human Rights, concluding that the defendant, as it relates to their defense, has the right, even in the presence of counsel, to participate in the questioning of witnesses and victims. Keywords: court party, witness, victim, direct examination, cross-examination.

У статті визначається сутність понять «прямий» і «перехресний» допит свідків і потерпілих. Аналізується проблема участі обвинуваченого (підсудного) в «прямому» і «перехресному» допиті свідків і потерпілих на підставі положень міжнародних конвенцій та практики Європейського суду з прав людини та наводиться висновок, що обвинувачений, оскільки він належить до сторони захисту, повинен мати право, навіть за наявності захисника, прийняти участь у допиті свідків і потерпілих. Ключові слова: суд, сторони, свідок, потерпілий, прямий допит, перехресний допит.
Особливості проведення прямого та перехресного судового допиту свідків та потерпілих